The kuroshio power plant - Chen, Falin (Lecture Notes in Energy, 2013)
By outlining a new design or the Kuroshio power plant, new approaches to turbine design, anchorage system planning, deep sea marine engineering and power plant operations and maintenance are explored and suggested. The impact on the local environment, particularly in the face of natural disasters, is also considered to provide a well rounded introduction to plan and build a 30MW pilot power plant.   Following a literature review, the six chapters of this book propose a conceptual design by focusing on the plant's core technologies and establish the separate analysis logics for turbine design and the relay platforms. This is tempered against the ecological impact of both the construction and operation of the plant.   These proposed technologies and plans can be further applied to power generation in other waters such as the Gulf Stream, the East Australian Current the Humboldt Current and the East Africa Coastal Current. Engineers, students and industry professionals are provided with a solid introduction to power plant technology as well as a design with specific real world applications